Silicon-carbon negative electrode material with structural and functional optimization, and preparation method and application thereof
Patent Information
- Application Number
- CN202510520849.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]然而,在多孔碳材料骨架内部均匀沉积硅纳米颗粒,虽然利用了碳骨架的导电性和结构稳定性来缓解硅在充放电过程中的体积膨胀问题,但这种方法在实际应用中仍存在一些缺陷和挑战:在沉积过程中,硅纳米颗粒可能发生团聚,形成较大的颗粒,导致体积膨胀加剧,增加SEI膜的形成和破裂,影响电池的循环稳定性
[0038]本发明实施例提供的表面功能性沉积改性的硅碳负极材料包括:多孔碳基体;沉积于多孔碳基体的孔隙及表面的具有夹层结构的硅碳沉积层;沉积于硅碳沉积层上的次表面功能层;以及位于最外层的碳包覆层。通过具有夹层结构的硅碳沉积层为硅源气体和碳源气体在多孔碳基体内交替气相沉积形成的纳米硅、碳的交替层状结构,进而通过多次交替沉积的碳层实现了在多孔碳孔道中对硅颗粒的隔离,有效控制降低了晶粒尺寸;同时,通过这种夹层结构中的碳层,还能够精准调控碳层夹层之间纳米硅的沉积,使得纳米硅的分布更加均匀,避免发生团聚,从而减小在循环过程中硅材料体积膨胀带来的影响,即降低了硅碳负极材料的体积膨胀;次表面功能层能在循环过程中发挥界面稳定、离子传输及应力缓冲作用,并与外层碳包覆结构紧密结合,能有效减少表面副反应、缓解材料体积膨胀,提高首效和循环性能。
Smart Images

Figure CN122992004A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of silicon-carbon anode material technology, and in particular to a silicon-carbon anode material with optimized structure and functionality, its preparation method, and its application. Background Technology
[0002] With the rapid development of consumer electronics, new energy vehicles and other fields, higher requirements are being placed on high-performance lithium-ion batteries, especially in terms of energy density, cycle life and charging speed. Although traditional graphite anode materials have good cycle stability and conductivity, their theoretical specific capacity of 372 mAh / g is close to their performance limit and cannot meet the needs of future high-energy-density batteries.
[0003] Silicon has become a strong contender for next-generation lithium-ion battery anode materials due to its high theoretical specific capacity of up to 4200 mAh / g, low lithium intercalation potential (approximately 0.3–0.5 V), abundant resources, and low cost. However, silicon undergoes a volume expansion of over 300% during charge and discharge, leading to material pulverization, electrode structure damage, and the formation of an unstable solid electrolyte interphase (SEI) film, resulting in irreversible capacity decay. Furthermore, silicon's inherent poor conductivity limits its performance under high-rate charge and discharge conditions.
[0004] To address these issues, researchers have proposed various strategies, including nanostructuring silicon materials, coating their surfaces with carbon layers, and combining them with highly conductive carbon materials. Among these, silicon-carbon composites combine silicon and carbon, leveraging silicon's high capacity while utilizing carbon's conductivity and structural stability. This effectively mitigates the volume expansion problem of silicon to some extent, improving the overall performance of the electrode. For example, uniformly depositing silicon nanoparticles within a porous carbon framework using vapor deposition technology can improve the battery's initial cycle efficiency, energy density, and cycle performance, while controlling cell expansion. This method has mature industrialization potential and has become an important research direction in the current new energy field.
[0005] However, while uniformly depositing silicon nanoparticles within a porous carbon framework leverages the conductivity and structural stability of the carbon framework to mitigate the volume expansion of silicon during charge and discharge, this method still presents some drawbacks and challenges in practical applications. During deposition, silicon nanoparticles may aggregate, forming larger particles that exacerbate volume expansion, increasing the formation and rupture of the SEI film and affecting the battery's cycle stability. Furthermore, despite the excellent conductivity of the carbon framework, uneven distribution of silicon particles or localized expansion disrupting the continuity of the carbon framework can obstruct electron and ion transport pathways, impacting the battery's rate performance.
[0006] While carbon coating can mitigate the volume changes of silicon during charging and discharging to some extent, the limited flexibility of the carbon layer makes it difficult to completely absorb and release the stress generated during lithium insertion / extraction. This can lead to cracks or peeling of the carbon layer, exposing silicon particles and increasing the likelihood of side reactions. If carbon coating fails to completely prevent silicon from contacting the electrolyte during charging and discharging, the SEI film will repeatedly rupture and rebuild during cycling, consuming electrolyte and lithium ions, resulting in reduced coulombic efficiency and cycle life.
[0007] Therefore, existing technologies cannot fully meet the industry's demand for silicon-carbon composite anode materials, and developing new silicon-carbon anode materials remains one of the key issues that the lithium-ion battery field urgently needs to overcome. Summary of the Invention
[0008] The purpose of this invention is to address the shortcomings of existing technologies by providing a silicon-carbon anode material with optimized structure and functionality, along with its preparation method and applications. This silicon-carbon anode material features a sandwich-structured silicon-carbon deposition layer. Through the carbon layer within the sandwich structure, the deposition of nano-silicon between the carbon layers can be precisely controlled, resulting in a more uniform distribution of nano-silicon, preventing agglomeration, and thus reducing the impact of silicon material volume expansion during cycling. Furthermore, this silicon-carbon anode material also possesses a subsurface functional layer and a carbon coating layer, which can stabilize the cross-section and reduce side reactions. Therefore, the silicon-carbon anode material of this invention exhibits advantages such as high initial efficiency and long cycle life.
[0009] To achieve the above objectives, in a first aspect, the present invention provides a silicon-carbon anode material with optimized structure and functionality, comprising:
[0010] Porous carbon matrix;
[0011] A silicon-carbon deposition layer with a sandwich structure deposited in the pores and surface of the porous carbon matrix;
[0012] Subsurface functional layers deposited on the silicon-carbon deposition layer; and
[0013] The outermost carbon coating layer.
[0014] Preferably, the silicon-carbon deposition layer with a sandwich structure is specifically a layered structure of alternating nano-silicon and carbon formed by alternating vapor-phase deposition of silicon source gas and carbon source gas in the porous carbon matrix.
[0015] Preferably, the particle size D50 of the porous carbon matrix is 3-20 μm; the pore size of the porous carbon matrix is less than or equal to 4 nm; wherein, the proportion of micropores in the porous carbon matrix is 20%-100%; and the micropores are pores with a diameter of less than 2 nm.
[0016] Preferably, the subsurface functional layer is formed by mixed gas deposition of a mixture of functional gas, silicon source gas and protective gas.
[0017] Preferably, the thickness of the silicon-carbon deposited layer with the sandwich structure is less than 4 nm;
[0018] The thickness of the subsurface functional layer is 5–50 nm;
[0019] The thickness of the carbon coating layer is 10–100 nm.
[0020] In a second aspect, embodiments of the present invention provide a method for preparing the structurally and functionally optimized silicon-carbon anode material as described in the first aspect above, comprising:
[0021] Step 1: Under a protective atmosphere, a first mixed gas consisting of silicon source gas and protective gas is introduced into a vapor deposition furnace with a built-in porous carbon matrix for vapor deposition.
[0022] Step 2: A second mixed gas consisting of carbon source gas and protective gas is introduced into the vapor deposition furnace for vapor deposition to obtain a silicon-carbon composite material after one deposition.
[0023] Step 3: Repeat steps 1 and 2 to obtain a silicon-carbon composite material after multiple depositions; through the multiple depositions, a silicon-carbon deposition layer with a sandwich structure is formed in the pores and surface of the porous carbon matrix.
[0024] Step 4: A third mixed gas consisting of functional gas, silicon source gas and protective gas is introduced into the vapor deposition furnace to deposit a subsurface functional layer on the silicon-carbon composite material after multiple depositions, thereby forming a subsurface functional layer on the silicon-carbon deposition layer with sandwich structure, and obtaining a silicon-carbon composite material with a subsurface functional layer.
[0025] Step 5: A fourth mixed gas, consisting of a carbon source gas and a protective gas, is introduced into the vapor deposition furnace to carbon-coat the silicon-carbon composite material with a subsurface functional layer, thereby obtaining the silicon-carbon anode material with optimized structure and functionality.
[0026] Preferably, the silicon source gas includes one or more of silane, methanesilane, ethylsilane, trichlorosilane, or silicon tetrachloride;
[0027] The protective gas includes one or more of nitrogen or argon;
[0028] The carbon source gas includes one or more of acetylene, methane, or propylene.
[0029] The functional gases include one or more of the following: acetylene, ethylene, propylene, methane, carbon dioxide, air, or ammonia;
[0030] The protective atmosphere is specifically a nitrogen atmosphere and / or an argon atmosphere.
[0031] Preferably, in step 1, the volume ratio of the silicon source gas and the protective gas constituting the first mixed gas is [2-23]:30; the vapor deposition temperature is 400℃-800℃, and the deposition time is 30-160min;
[0032] In step 2, the volume ratio of the carbon source gas to the protective gas constituting the second mixed gas is 18:[2-6]; the vapor deposition temperature is 400℃-800℃, and the deposition time is 10-180min;
[0033] In step 3, the number of times the execution is repeated is 1-3 times; the number of times it is repeated is 2-4 times.
[0034] In step 4, the volume ratio of the functional gas, silicon source gas, and protective gas constituting the third mixed gas is [5-10]:[2-10]:30; the vapor deposition temperature is 400℃-800℃, and the deposition time is 2-10 hours.
[0035] In step 5, the flow ratio of the carbon source gas and the protective gas constituting the fourth mixed gas is [20-50]:50; the carbon coating temperature is 400℃-800℃, and the carbon coating time is 2-4 hours.
[0036] Thirdly, embodiments of the present invention provide a negative electrode sheet, comprising the structurally and functionally optimized silicon-carbon negative electrode material described in the first aspect above, or comprising the structurally and functionally optimized silicon-carbon negative electrode material prepared by the preparation method described in the second aspect.
[0037] Fourthly, embodiments of the present invention provide a lithium battery comprising the structurally and functionally optimized silicon-carbon anode material as described in the first aspect, or the structurally and functionally optimized silicon-carbon anode material prepared by the preparation method described in the second aspect.
[0038] The surface-functionalized silicon-carbon anode material provided in this invention includes: a porous carbon matrix; a sandwich-structured silicon-carbon deposition layer deposited in the pores and surface of the porous carbon matrix; a subsurface functional layer deposited on the silicon-carbon deposition layer; and an outermost carbon coating layer. The sandwich-structured silicon-carbon deposition layer is an alternating layered structure of nano-silicon and carbon formed by the alternating vapor-phase deposition of silicon and carbon source gases within the porous carbon matrix. The multiple alternating carbon layers isolate silicon particles within the porous carbon channels, effectively controlling and reducing grain size. Simultaneously, the carbon layers in this sandwich structure allow for precise control of nano-silicon deposition between the carbon layers, resulting in a more uniform distribution of nano-silicon, preventing agglomeration, and reducing the impact of silicon material volume expansion during cycling, thus reducing the volume expansion of the silicon-carbon anode material. The subsurface functional layer plays a role in interface stabilization, ion transport, and stress buffering during cycling, and is tightly integrated with the outer carbon coating structure, effectively reducing surface side reactions, alleviating material volume expansion, and improving first-efficiency and cycle performance. Attached Figure Description
[0039] Figure 1 A partial structural schematic diagram of a silicon-carbon anode material with optimized structural functionality provided in an embodiment of the present invention;
[0040] Figure 2 A flowchart illustrating the preparation method of the structurally and functionally optimized silicon-carbon anode material provided in this embodiment of the invention. Detailed Implementation
[0041] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0042] This invention provides a silicon-carbon anode material with optimized structure and functionality, its preparation method, and its application.
[0043] The silicon-carbon anode material of the present invention includes:
[0044] Porous carbon matrix;
[0045] A silicon-carbon deposition layer with a sandwich structure deposited in the pores and surface of a porous carbon matrix;
[0046] Subsurface functional layers deposited on silicon-carbon deposition layers; and
[0047] The outermost carbon coating layer.
[0048] Figure 1 This is a partial structural schematic diagram of a silicon-carbon anode material with optimized structural functionality provided in an embodiment of the present invention. (Combined with...) Figure 1 The structure of the silicon-carbon anode material of this invention can be clearly understood.
[0049] The particle size D50 of the porous carbon matrix is 3-20 μm; the pore size of the porous carbon matrix is less than or equal to 4 nm, preferably 1-4 nm. Among the pores of the porous carbon matrix, the proportion of micropores is 20%-100%; micropores are pores with a diameter of less than 2 nm.
[0050] The particle size D50 of a porous carbon matrix refers to the median particle size of the porous carbon matrix material, which can be the median value sorted by volume, mass, or quantity. In this example, it is the median particle size sorted by quantity, representing the particle size of the porous carbon matrix that accounts for 50% of the total particle size distribution. Particle size D50 is a well-known concept in the art. The particle size D50 of the material provided in the embodiments of this invention can be determined using instruments and conventional methods known in the art. Specifically, in all embodiments of this invention, a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK, is used to determine the particle size D50.
[0051] Pore size refers to the diameter or characteristic size of the pores inside carbon materials, and is an important parameter describing their pore structure. Pore size testing employs the gas adsorption method and is performed using a fully automated specific surface area and porosity analyzer, ASAP2460.
[0052] In the structure of this invention, a sandwich-structured silicon-carbon deposition layer is formed by vapor phase deposition on the pores and surface of a porous carbon matrix, and more importantly, it is located within the pores. Specifically, it is a layered structure of alternating nano-silicon and carbon formed by alternating vapor phase deposition of silicon source gas and carbon source gas within a porous carbon matrix. That is, a structure in which a nano-silicon deposition layer is sandwiched between every two adjacent carbon layers. The silicon source gas can be one or more of silane, methane, silane, trichlorosilane, or silicon tetrachloride, and the carbon source gas can be one or more of acetylene, methane, or propylene.
[0053] The subsurface functional layer is located between a sandwich-structured silicon-carbon deposition layer and a carbon coating layer. It is formed through vapor deposition of a mixture of functional gas and silicon source gas. Different functional gases can be selected to form subsurface functional layers with different focuses. Functional gases can be one or more of acetylene, ethylene, propylene, methane, carbon dioxide, air, or ammonia. Co-deposition of silicon source gas, functional carbon source gas, and protective gas can produce SiC-based or Si-CN composite amorphous functional layers. Depending on the choice and combination of gas sources, it can specifically include: amorphous or nanocrystalline SiC, amorphous carbon, doped carbon / silicon-carbon (such as N-doped carbon / silicon-carbon, O-doped carbon / silicon-carbon), and possibly small amounts of silicon-oxygen compounds or silicon-nitrogen compounds.
[0054] In this specification, several typical structural components contained in the subsurface functional layer are described.
[0055] Amorphous or nanocrystalline silicon carbide (SiC): Formed under conditions where silicon and carbon source gases coexist, it is the most important component. As a phase that combines chemical stability and mechanical strength, it can enhance the mechanical stability of the overall composite structure, effectively suppress interface detachment and pulverization during lithium-ion intercalation / deintercalation, and improve interface stability.
[0056] Doped carbon / silicon carbon (such as nitrogen-doped carbon / silicon carbon, oxygen-doped carbon / silicon carbon): When a nitrogen- or oxygen-containing gas such as ammonia, carbon dioxide or air is introduced into the functional gas, nitrogen- or oxygen-containing functional groups can be introduced into the deposited carbon or silicon carbon, thereby improving electronic conductivity and helping to stabilize the SEI film structure.
[0057] Amorphous silicon oxide (SiOx) or silicon nitride oxide (Si-NO): formed by the interaction of silicon source with air, carbon dioxide or ammonia, used to construct an interface barrier structure with high electrochemical stability and suppress the occurrence of side reactions;
[0058] Amorphous carbon: mainly formed by the cracking of carbon sources such as acetylene, ethylene, propylene, and methane, it can significantly improve the electronic conductivity of silicon-carbon composite materials and, to a certain extent, buffer the volume expansion of silicon during lithium insertion and extraction, preventing the electrode structure from cracking.
[0059] Those skilled in the art can select appropriate functional gases, silicon source gases, and protective gases to form a mixed gas according to the required performance of the silicon-carbon anode material, so as to obtain a subsurface functional layer with the required functions.
[0060] In the structurally and functionally optimized silicon-carbon anode material of the present invention, the thickness of the silicon-carbon deposited layer with sandwich structure is less than 4 nm; the thickness of the subsurface functional layer is 5–50 nm; and the thickness of the carbon coating layer is 10–100 nm.
[0061] The surface-functionalized silicon-carbon anode material provided in this invention includes: a porous carbon matrix; a sandwich-structured silicon-carbon deposition layer deposited in the pores and surface of the porous carbon matrix; a subsurface functional layer deposited on the silicon-carbon deposition layer; and an outermost carbon coating layer. The sandwich-structured silicon-carbon deposition layer is an alternating layered structure of nano-silicon and carbon formed by the alternating vapor-phase deposition of silicon and carbon source gases within the porous carbon matrix. The multiple alternating carbon layers isolate silicon particles within the porous carbon channels, effectively controlling and reducing grain size. Simultaneously, the carbon layers in this sandwich structure allow for precise control of nano-silicon deposition between the carbon layers, resulting in a more uniform distribution of nano-silicon, preventing agglomeration, and reducing the impact of silicon material volume expansion during cycling, thus reducing the volume expansion of the silicon-carbon anode material. The subsurface functional layer plays a role in interface stabilization, ion transport, and stress buffering during cycling, and is tightly integrated with the outer carbon coating structure, effectively reducing surface side reactions, alleviating material volume expansion, and improving first-efficiency and cycle performance.
[0062] In this embodiment of the invention, a method for preparing the above-mentioned structurally and functionally optimized silicon-carbon anode material is provided, the main steps of which are illustrated below. Figure 2 As shown, it includes the following steps:
[0063] Step 110: Under a protective atmosphere, a first mixed gas consisting of silicon source gas and protective gas is introduced into a vapor deposition furnace with a built-in porous carbon matrix for vapor deposition.
[0064] In step 110, the volume ratio of the silicon source gas and the protective gas constituting the first mixed gas is [2-23]:30; the vapor deposition temperature is 400℃-800℃, and the deposition time is 30-160min;
[0065] Uniform deposition of silicon nanoparticles within a porous carbon matrix facilitates the loading of high-capacity active materials and "fixes" silicon within the conductive network through carbon channels, mitigating silicon pulverization and interfacial side reactions.
[0066] Step 120: A second mixed gas consisting of carbon source gas and protective gas is introduced into a vapor deposition furnace for vapor deposition to obtain a silicon-carbon composite material after one deposition.
[0067] In step 120, the volume ratio of the carbon source gas to the protective gas constituting the second mixed gas is 18:[2-6]; the temperature of vapor deposition is 400℃-800℃, and the deposition time is 10-180min;
[0068] Introducing carbon source gas can form a carbon layer structure on the surface of silicon particles, improving electronic conductivity and forming the first carbon isolation layer, thereby providing a flexible buffer function during lithiation / delithiation.
[0069] Repeat steps 110 and 120. The number of times to repeat is 1-3; that is, multiple deposition means that each time step 110 and step 120 are executed, the deposition count is 1, and the total number of depositions is 2-4.
[0070] After repeating steps 110 and 120 several times, a silicon-carbon composite material with multiple depositions is obtained; through multiple depositions, a silicon-carbon deposition layer with a sandwich structure is formed in the pores and surface of the porous carbon matrix.
[0071] By alternately executing steps 110 and 120, and combining them with the initial porous carbon matrix structure, a C / Si / C... sandwich structure can be constructed layer by layer inside and on the surface of the carbon skeleton, achieving a gradient silicon distribution and multi-layer stress buffering. The expansion stress is dispersed by the interlayer interface, thereby improving the overall mechanical toughness and structural stability of the electrode.
[0072] Step 130: A third mixed gas consisting of functional gas, silicon source gas and protective gas is introduced into a vapor deposition furnace to deposit a subsurface functional layer on the silicon-carbon composite material after multiple depositions, thereby forming a subsurface functional layer on the silicon-carbon deposition layer with a sandwich structure, and obtaining a silicon-carbon composite material with a subsurface functional layer.
[0073] In step 130, the volume ratio of the functional gas, silicon source gas, and protective gas constituting the third mixed gas is [5-10]:[2-10]:30; the vapor deposition temperature is 400℃-800℃, and the deposition time is 2-10 hours.
[0074] By depositing a functional thin film on the outermost carbon coating layer, it is beneficial to enhance interfacial chemical passivation, regulate SEI formation, and promote Li+ transport.
[0075] Step 140: A fourth mixed gas consisting of carbon source gas and protective gas is introduced into a vapor phase deposition furnace to carbon-coat the silicon-carbon composite material with a subsurface functional layer, thereby obtaining a silicon-carbon anode material with optimized structure and functionality.
[0076] In step 140, the flow rate ratio of the carbon source gas and the protective gas constituting the fourth mixed gas is [20-50]:50; the carbon coating temperature is 400℃-800℃, and the carbon coating time is 2-4 hours.
[0077] By depositing a continuous carbon coating layer on the outermost layer, electrolyte erosion can be prevented and expansion can be further mitigated.
[0078] In the above preparation method, the silicon source gas includes one or more of silane, silane, disilane, trichlorosilane, or silicon tetrachloride; the protective gas includes one or more of nitrogen or argon; the carbon source gas includes one or more of acetylene, methane, or propylene; the functional gas includes one or more of acetylene, ethylene, propylene, methane, carbon dioxide, air, or ammonia; and the protective atmosphere is specifically a nitrogen atmosphere and / or an argon atmosphere.
[0079] By adjusting and selecting specific functional gases, the specific structure and composition of the subsurface functional layer can be adjusted. For example, it may include amorphous or nanocrystalline silicon carbide (SiC), doped carbon / silicon-carbon (such as nitrogen-doped carbon / silicon-carbon, oxygen-doped carbon / silicon-carbon), amorphous silicon oxide (SiOx) or silicon nitride oxide (Si-NO), amorphous carbon, etc. Those skilled in the art can select or combine the functional gases given above according to the performance of the required silicon-carbon anode material to obtain the subsurface functional layer with the required functions and properties.
[0080] The above-mentioned preparation method of the present invention constructs a silicon-carbon composite material with a fourfold structure of "porous carbon skeleton - sandwich silicon-carbon deposition layer - subsurface functional layer - outer carbon shell" by sequentially performing silicon deposition, carbon deposition, subsurface functional layer deposition and carbon coating treatment in a porous carbon matrix, thereby achieving synergistic regulation of structure and interface.
[0081] The sandwich-type silicon-carbon deposition structure with multiple alternating depositions effectively controls the deposition and distribution of silicon particles in the porous carbon channels, reducing silicon particle size and avoiding large particle agglomeration. The sandwich structure also effectively mitigates the volume expansion of silicon during charge and discharge, improving the structural integrity and mechanical stability of the composite material during cycling. The subsurface functional layer, located between the outer carbon layer and the silicon-carbon sandwich, induces the formation of a stable interface layer before the first charge and discharge, suppressing the formation of unstable SEIs and improving the initial coulombic efficiency and extending cycle life. The outermost carbon coating layer enhances the overall conductivity and acts as an encapsulation and buffer, further improving the material's rate performance and interface stability. This method employs a vapor phase deposition process throughout, enabling precise control over deposition thickness, composition ratio, and structural morphology, demonstrating good repeatability and promising industrial application prospects.
[0082] In summary, this method significantly improves the overall electrochemical performance and cycle stability of silicon-carbon anode materials, providing reliable technical support for the practical application of high-energy-density lithium-ion battery anode materials.
[0083] The silicon-carbon anode material with optimized structure and function proposed above and prepared by the preparation method of this invention can be used to prepare anode sheets and for use in lithium batteries, especially lithium-ion batteries.
[0084] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0085] Example 1
[0086] S1, Under a nitrogen atmosphere, 5 kg of porous carbon was placed in a vapor deposition furnace and heated to 500 °C at a heating rate of 5 °C / min and a nitrogen flow rate of 50 L / min. After the temperature stabilized, a mixture of silane and nitrogen with a total flow rate of 90 L / min and a flow ratio of 15:30 was introduced into the vapor deposition furnace and continuously circulated for 10 min to deposit silicon.
[0087] S2, After the deposition in step S1 is completed, the temperature is maintained at 500℃, and a mixture of acetylene and nitrogen with a total flow rate of 46L / min and a flow ratio of 18:5 is introduced into the vapor phase deposition furnace and the gas is continuously introduced for 10 minutes to perform carbon layer deposition.
[0088] S3, repeat steps S1 and S2 for a total of 3 times;
[0089] S4. The vapor deposition furnace is heated to 550°C in a nitrogen atmosphere at a heating rate of 5°C / min and a nitrogen flow rate of 50 L / min. Subsequently, a mixture of acetylene, silane, and nitrogen with a total flow rate of 90 L / min and a flow ratio of 5:10:30 is introduced to perform functional layer deposition at a deposition temperature of 550°C for 2 hours.
[0090] S5. After the deposition in step S4 is completed, the temperature is maintained at 550°C, and a mixture of acetylene and nitrogen with a total flow rate of 80 L / min and a flow ratio of 30:50 is introduced. The mixture is kept at 550°C for 2 hours to obtain the silicon-carbon anode material of Example 1.
[0091] The silicon-carbon anode material prepared in this embodiment was used as the anode active material to prepare the anode sheet, and then assembled into a coin cell in a glove box. The test was then carried out. The specific process is as follows:
[0092] The silicon-carbon composite anode material obtained in this embodiment, acetylene black, and carboxymethyl cellulose (CMC) were thoroughly ground in a mortar at a mass ratio of 9:0.5:0.5. Deionized water was then added, and the mixture was pulped in a pulping machine to form a slurry. This slurry was then coated onto a copper foil current collector and dried in a vacuum oven at 85°C for 10 hours. The dried electrode was then cut into 14mm diameter discs to serve as the anode material for lithium-ion batteries.
[0093] A solution of ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) containing 1 mol / L lithium hexafluorophosphate (LiPF6) (volume ratio v:v:v = 1:1:1) was used as the electrolyte. A polyethylene membrane was used as the separator, and a lithium electrode was used as the counter electrode in the coin cell.
[0094] The electrochemical performance of the battery was evaluated by testing it on the Blue Battery Testing System.
[0095] Capacity retention after 200 cycles was tested under the following conditions: voltage window of 0.01V-2V; discharge rate of 0.1C; lower limit of discharge voltage window: 0.01V. The capacity retention after 200 cycles is recorded in Table 1.
[0096] The 0.8V first-cycle efficiency (%) was determined under the following conditions: voltage window 0.8V-2V; discharge rate 0.1C; initial charging to the upper limit voltage of 2V, followed by 0.1C discharge to the lower limit voltage of 0.8V. The initial charge capacity (mAh / g) and initial discharge capacity (mAh / g) were recorded, and the ratio of the initial discharge specific capacity to the initial charge specific capacity was calculated; this is the 0.8V first-cycle efficiency. This parameter reflects the coulombic efficiency of the material during its first cycle. A higher first-cycle efficiency indicates fewer irreversible reactions in the material initially, resulting in higher initial energy utilization in practical applications.
[0097] The initial expansion rate of the negative electrode in a coin cell was tested using the following method: At room temperature, the prepared negative electrode sheet was ion-beam cut, and the cross-section was photographed using a scanning electron microscope (SEM). The thickness of the negative electrode sheet before assembly into the coin cell was recorded as T1; the thickness of the copper foil current collector substrate was recorded as T2. The coin cell was fully charged at a current density of 0.1C and a charging cutoff voltage of 2V. The cell was then disassembled in a glove box, the negative electrode sheet was removed, and after ion-beam cutting, the cross-section was photographed using an SEM, and the thickness of the negative electrode sheet at this point was measured and recorded as T3. The initial expansion rate was then calculated using the formula: Initial Expansion Rate = (T3 - T1) / (T1 - T2) × 100%. The results are listed in Table 1.
[0098] Example 2
[0099] S1, Under a nitrogen atmosphere, 5 kg of porous carbon was placed in a vapor deposition furnace and heated to 500 °C at a heating rate of 5 °C / min and a nitrogen flow rate of 50 L / min. After the temperature stabilized, a mixture of silane and nitrogen with a total flow rate of 90 L / min and a flow ratio of 15:30 was introduced into the vapor deposition furnace and continuously circulated for 10 min to deposit silicon.
[0100] S2, After the deposition in step S1 is completed, the temperature is maintained at 500℃, and a mixture of acetylene and nitrogen with a total flow rate of 46L / min and a flow ratio of 18:5 is introduced into the vapor phase deposition furnace and the gas is continuously introduced for 10 minutes to perform carbon layer deposition.
[0101] S3, repeat steps S1 and S2, for a total of 2 times;
[0102] S4. The vapor deposition furnace is heated to 550°C in a nitrogen atmosphere at a heating rate of 5°C / min and a nitrogen flow rate of 50 L / min. Subsequently, a mixture of acetylene, silane, and nitrogen with a total flow rate of 90 L / min and a flow ratio of 5:10:30 is introduced to perform functional layer deposition at a deposition temperature of 550°C for 2 hours.
[0103] S5. After the deposition in step S4 is completed, the temperature is maintained at 550°C, and a mixture of acetylene and nitrogen with a total flow rate of 80 L / min and a flow ratio of 30:50 is introduced. The mixture is kept at 550°C for 2 hours to obtain the silicon-carbon anode material of Example 2.
[0104] The half-cell assembly and testing are the same as in Example 1.
[0105] Example 3
[0106] S1, Under a nitrogen atmosphere, 5 kg of porous carbon was placed in a vapor deposition furnace and heated to 500 °C at a heating rate of 5 °C / min and a nitrogen flow rate of 50 L / min. After the temperature stabilized, a mixture of silane and nitrogen with a total flow rate of 90 L / min and a flow ratio of 15:30 was introduced into the vapor deposition furnace and continuously circulated for 10 min to deposit silicon.
[0107] S2, After the deposition in step S1 is completed, the temperature is maintained at 500℃, and a mixture of acetylene and nitrogen with a total flow rate of 46L / min and a flow ratio of 18:5 is introduced into the vapor phase deposition furnace and the gas is continuously introduced for 10 minutes to perform carbon layer deposition.
[0108] S3, repeat steps S1 and S2 for a total of 3 times;
[0109] S4. The vapor deposition furnace is heated to 550°C in a nitrogen atmosphere at a heating rate of 5°C / min and a nitrogen flow rate of 50 L / min. Subsequently, a mixture of ammonia, silane, and nitrogen with a total flow rate of 90 L / min and a flow ratio of 5:10:30 is introduced to perform functional layer deposition at a deposition temperature of 550°C for 2 hours.
[0110] S5. After the deposition in step S4 is completed, the temperature is maintained at 550°C, and a mixture of acetylene and nitrogen with a total flow rate of 80 L / min and a flow ratio of 30:50 is introduced. The mixture is kept at 550°C for 2 hours to obtain the silicon-carbon anode material of Example 3.
[0111] The half-cell assembly and testing are the same as in Example 1.
[0112] Example 4
[0113] S1, Under a nitrogen atmosphere, 5 kg of porous carbon was placed in a vapor deposition furnace and heated to 500 °C at a heating rate of 5 °C / min and a nitrogen flow rate of 50 L / min. After the temperature stabilized, a mixture of silane and nitrogen with a total flow rate of 90 L / min and a flow ratio of 15:30 was introduced into the vapor deposition furnace and continuously circulated for 10 min to deposit silicon.
[0114] S2, After the deposition in step S1 is completed, the temperature is maintained at 500℃, and a mixture of acetylene and nitrogen with a total flow rate of 46L / min and a flow ratio of 18:5 is introduced into the vapor phase deposition furnace and the gas is continuously introduced for 10 minutes to perform carbon layer deposition.
[0115] S3, repeat steps S1 and S2 for a total of 3 times;
[0116] S4. The vapor deposition furnace is heated to 550°C in a nitrogen atmosphere at a heating rate of 5°C / min and a nitrogen flow rate of 50 L / min. Subsequently, a mixture of carbon dioxide, silane, and nitrogen with a total flow rate of 90 L / min and a flow ratio of 5:10:30 is introduced to perform functional layer deposition at a deposition temperature of 550°C for 2 hours.
[0117] S5. After the deposition in step S4 is completed, the temperature is maintained at 550°C, and a mixture of acetylene and nitrogen with a total flow rate of 80 L / min and a flow ratio of 30:50 is introduced. The mixture is kept at 550°C for 2 hours to obtain the silicon-carbon anode material of Example 4.
[0118] The half-cell assembly and testing are the same as in Example 1.
[0119] For better comparative illustration, the present invention also relates to the following comparative examples 1 and 2.
[0120] Comparative Example 1
[0121] S1, Under a nitrogen atmosphere, 5 kg of porous carbon was placed in a vapor deposition furnace and heated to 500 °C at a heating rate of 5 °C / min and a nitrogen flow rate of 50 L / min. After the temperature stabilized, a mixture of silane and nitrogen with a total flow rate of 90 L / min and a flow ratio of 15:30 was introduced into the vapor deposition furnace and continuously circulated for 10 min to deposit silicon.
[0122] S2, After the deposition in step S1 is completed, the temperature is maintained at 500℃, and a mixture of acetylene and nitrogen with a total flow rate of 46L / min and a flow ratio of 18:5 is introduced into the vapor phase deposition furnace and the gas is continuously introduced for 10 minutes to perform carbon layer deposition.
[0123] S3, the vapor deposition furnace is heated to 550℃ in a nitrogen atmosphere at a heating rate of 5℃ / min and a nitrogen flow rate of 50L / min. Subsequently, a mixture of acetylene, silane, and nitrogen with a total flow rate of 90L / min and a flow ratio of 5:10:30 is introduced to perform functional layer deposition at a deposition temperature of 550℃ for 2 hours.
[0124] S4. After the deposition in step S3 is completed, the temperature is maintained at 550℃, and a mixture of acetylene and nitrogen with a total flow rate of 80L / min and a flow ratio of 30:50 is introduced. The mixture is kept at 550℃ for 2 hours to obtain the silicon-carbon anode material of Comparative Example 1.
[0125] The half-cell assembly and testing are the same as in Example 1.
[0126] Comparative Example 2
[0127] S1, Under a nitrogen atmosphere, 5 kg of porous carbon was placed in a vapor deposition furnace and heated to 500 °C at a heating rate of 5 °C / min and a nitrogen flow rate of 50 L / min. After the temperature stabilized, a mixture of silane and nitrogen with a total flow rate of 90 L / min and a flow ratio of 15:30 was introduced into the vapor deposition furnace and continuously circulated for 10 min to deposit silicon.
[0128] S2, After the deposition in step S1 is completed, the temperature is maintained at 500℃, and a mixture of acetylene and nitrogen with a total flow rate of 46L / min and a flow ratio of 18:5 is introduced into the vapor phase deposition furnace and the gas is continuously introduced for 10 minutes to perform carbon layer deposition.
[0129] S3, repeat steps S1 and S2 for a total of 3 times;
[0130] S4. After the deposition in step S3 is completed, the temperature is maintained at 550℃, and a mixture of acetylene and nitrogen with a total flow rate of 80L / min and a flow ratio of 30:50 is introduced. The mixture is kept at 550℃ for 2 hours to obtain the silicon-carbon anode material of Comparative Example 2.
[0131] The half-cell assembly and testing are the same as in Example 1.
[0132] The test data for each embodiment and comparative example are detailed in Table 1 below.
[0133]
[0134] The data comparison above shows that:
[0135] Examples 1-4 exhibited excellent cycle stability with capacity retention ranging from 89.6% to 93.6%, compared to only 86.4% and 84.1% for Comparative Examples 1 and 2, respectively, showing a significant decrease. The first-cycle expansion rate of Examples 1-4 ranged from 29.7% to 31.3%, while Comparative Examples 1 and 2 were 37.3% and 34.4%, respectively, significantly higher than the Examples 1-4. The first-cycle efficiency at 0.8V was 81.9% to 84.2% for Examples 1-4, while Comparative Examples 1 and 2 were 78.6% and 76.3%, respectively, significantly lower.
[0136] As can be seen, the sandwich structure and subsurface functional layer formed in the embodiments effectively buffer the volume expansion of silicon, improve structural stability, and significantly delay capacity decay. In the embodiments, by optimizing the vapor deposition formation of the sandwich structure within porous carbon pores and adding a subsurface functional layer for regulation, the initial irreversible reaction is reduced, improving initial energy efficiency and long-term cycling performance.
[0137] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A silicon-carbon anode material with optimized structure and functionality, characterized in that, The silicon-carbon anode material includes: Porous carbon matrix; A silicon-carbon deposition layer with a sandwich structure deposited in the pores and surface of the porous carbon matrix; Subsurface functional layers deposited on the silicon-carbon deposition layer; and The outermost carbon coating layer.
2. The silicon-carbon anode material according to claim 1, characterized in that, The porous carbon matrix has a particle size D50 of 3-20 μm; the pore size of the porous carbon matrix is less than or equal to 4 nm; wherein, the proportion of micropores in the porous carbon matrix is 20%-100%; and the micropores are pores with a diameter of less than 2 nm.
3. The silicon-carbon anode material according to claim 1, characterized in that, The silicon-carbon deposition layer with a sandwich structure is specifically a layered structure of alternating nano-silicon and carbon formed by alternating vapor-phase deposition of silicon source gas and carbon source gas in the porous carbon matrix.
4. The silicon-carbon anode material according to claim 1, characterized in that, The subsurface functional layer is formed by mixed gas deposition of a mixture of functional gas, silicon source gas, and protective gas.
5. The silicon-carbon anode material according to claim 1, characterized in that, The thickness of the silicon-carbon deposition layer with the sandwich structure is less than 4 nm; The thickness of the subsurface functional layer is 5–50 nm; The thickness of the carbon coating layer is 10–100 nm.
6. A method for preparing a silicon-carbon anode material with optimized structure and function as described in any one of claims 1-5, characterized in that, The preparation method includes: Step 1: Under a protective atmosphere, a first mixed gas consisting of silicon source gas and protective gas is introduced into a vapor deposition furnace with a built-in porous carbon matrix for vapor deposition. Step 2: A second mixed gas consisting of carbon source gas and protective gas is introduced into the vapor deposition furnace for vapor deposition to obtain a silicon-carbon composite material after one deposition. Step 3: Repeat steps 1 and 2 to obtain a silicon-carbon composite material after multiple depositions; through the multiple depositions, a silicon-carbon deposition layer with a sandwich structure is formed in the pores and surface of the porous carbon matrix. Step 4: A third mixed gas consisting of functional gas, silicon source gas and protective gas is introduced into the vapor deposition furnace to deposit a subsurface functional layer on the silicon-carbon composite material after multiple depositions, thereby forming a subsurface functional layer on the silicon-carbon deposition layer with sandwich structure, and obtaining a silicon-carbon composite material with a subsurface functional layer. Step 5: A fourth mixed gas, consisting of a carbon source gas and a protective gas, is introduced into the vapor deposition furnace to carbon-coat the silicon-carbon composite material with a subsurface functional layer, thereby obtaining the silicon-carbon anode material with optimized structure and functionality.
7. The preparation method according to claim 6, characterized in that, The silicon source gas includes one or more of the following: silane, methanesilane, ethylsilane, trichlorosilane, or silicon tetrachloride; The protective gas includes one or more of nitrogen or argon; The carbon source gas includes one or more of acetylene, methane, or propylene. The functional gases include one or more of the following: acetylene, ethylene, propylene, methane, carbon dioxide, air, or ammonia; The protective atmosphere is specifically a nitrogen atmosphere and / or an argon atmosphere.
8. The preparation method according to claim 6, characterized in that, In step 1, the volume ratio of silicon source gas to protective gas in the first mixed gas is [2-23]:30; the vapor deposition temperature is 400℃-800℃, and the deposition time is 30-160min; In step 2, the volume ratio of the carbon source gas to the protective gas constituting the second mixed gas is 18:[2-6]; the vapor deposition temperature is 400℃-800℃, and the deposition time is 10-180min; In step 3, the number of times the execution is repeated is 1-3 times; the number of times it is repeated is 2-4 times. In step 4, the volume ratio of the functional gas, silicon source gas, and protective gas constituting the third mixed gas is [5-10]:[2-10]:30; the vapor deposition temperature is 400℃-800℃, and the deposition time is 2-10 hours. In step 5, the flow ratio of the carbon source gas and the protective gas constituting the fourth mixed gas is [20-50]:50; the carbon coating temperature is 400℃-800℃, and the carbon coating time is 2-4 hours.
9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the structurally and functionally optimized silicon-carbon negative electrode material according to any one of claims 1-5, or the structurally and functionally optimized silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 6-8.
10. A lithium battery, characterized in that, The lithium battery includes the structurally and functionally optimized silicon-carbon anode material as described in any one of claims 1-5, or the structurally and functionally optimized silicon-carbon anode material prepared by the preparation method described in any one of claims 6-8.